Matrix Approach to Modelling of Polarized Radiation Transfer in Heterogeneous Systems - Sushkevich, T. A.; Strelkov, S. A.; Maksakova, S. V. (Matrix Methods: Theory, Algorithms And Applications, 2010)
The general vector boundary-value problem for the integro-differential kinetic Boltzmann equation, which describes the polarized radiation transfer in a heterogeneous plane layer with a horizontally non-homogeneous and anisotropically reflective boundary, cannot be solved by the finite-difference methods. A mathematical model is proposed and justified that gives an asymptotically exact solution of the boundary-value problem in the class of the functions of slow growth. The new model is constructed by the influence function method and is efficient for algorithms using parallel computing.